PENERAPAN METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV MI AL-IKHLAS TANJUNG MEDAN KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Damanhuri Daud; Hendri Marhadi; Marlia Marlia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACKThis research aims to improve grade IV student’s social science learning achievement at MI Al-Ikhlas Tanjung Medan Kecamatan Tambusai Utara academic year 2013/2014 through “Application of the method of giving a task”. Setting of the problem is “is the application of the method of giving a task can improve grade IV student’s social science learning achievement at MI Al-Ikhlas Tanjung Medan”. This research was conducted in February. The numbers of students are 25 students which contains of 13 boys and 12 girls. This research is classroom action research which contains of three cycles. Each cycle consist of 2 meeting. Parameter of the research is involved students learning achievement after the action in each cycle (daily test I, II, III). Instrument of the research contains of learning tools (syllabus, RPP, LKS, learning result paper sheet), observation of student and teacher activity sheet. Data of the research will analyze descriptively. Research data show that learning achievement has increased. Where prior to the application of the methods of giving a task as much as any 12 students (48%) scored daily test is above or equal to the minimum completeness criteria (KKM). It was improved to 60% after using the application of the method of giving a task in first cycle. In the second cycle increased to 80% and in the third cycle increased to 96%. Activities of the students during the learning process (I, II, III cycles) is can be categorized very well by an average 96.87%. From the explanation above shows that application of the method of giving a task can be improving grade IV student’s social science learning achievement at MI Al-Ikhlas Tanjung Medan.Keyword: the method of giving a task, learning achievement